Examining the impact of IC components on BSE Firms: Using Dynamic Panel Data (Trinity Journal of Management, IT & Media (TJMITM), 2022)
In recent years, the economy has shifted from production to knowledge-based. Intellectual capital has gained importance in these years. Intellectual capital is the organization's hidden cost that helps generate value. The purpose of the study is to examine the impact of intellectual capital on the financial performance of 294 BSE firms. The study collected the Capitaline database data for 2010-2020. The Dynamic Panel Data regression statistical technique has been applied to analyze the data as there was an endogeneity problem. The results revealed that human capital efficiency and structural capital efficiency have an impact on the profitability of the organization. The profitability has been calculated using return on assets. However, on the other hand, it has been found that physical capital only impacts the market value to book value, and intellectual capital doesn't have any impact. The study is beneficial for the management to disclose intellectual capital as it will help them to show the true picture of the organization, thus increasing the profitability.
Keywords: Intellectual Capital; Dynamic panel data; Endogeneity; BSE; VAICTM